ANALISIS PERKEBUNAN ORGANIK SEBAGAI SUMBER BELAJAR EKOSISTEM - mia, Cholvis; widowati, Hening (Universitas Muhammadiyah Metro, 2020)
Abstract: The current curriculum implementation in 2013 emphasizes learning based on the application of daily life in accordance with scientific learning. This study aims to observe and analyze the potential of learning resources in the Organic Garden 23 Karang Rejo Metro City with the subject matter of Ecosystem Class X SMA. The results of the study of the potential sources of learning obtained by biotic components, namely types of vegetable plants, types of flowering plants, insects and abiotic components that form food webs and energy cycles. Based on the criteria for making teaching materials consisting of clarity of potential, conformity with learning objectives, clarity of objectives, clarity of information that can be revealed, clarity of exploration guidelines, clarity of acquisition that is expected to study learning resources for packaging teaching materials can be used as a reference for the development of teaching materials based on local potential through adjustments to the 2013 curriculum, characteristics and needs of students.